BENTUK PENYAJIAN TARI PAGAR PENGANTIN DI SANGGAR BEFA DANCEKELURAHAN TANJUNG KUPANG KABUPATEN EMPAT LAWANG - Lerin Rili Andrayani; Mansyur, Herlinda (Avant-garde: Jurnal Ilmiah Pendidikan Seni Pertunjukan, 2026)
This study aims to describe the "Presentation Form of the Pagar Pengantin Dance at the Befa Dance Studio in Tanjung Kupang Village, Empat Lawang Regency." This qualitative research uses descriptive methods. The research instrument was the researcher herself, assisted by supporting instruments such as stationery and a camera. Data were collected through observation, literature review, interviews, and documentation. Data analysis involved selecting relevant data according to the problem being discussed. The results indicate that the Pagar Pengantin dance at the Befa Dance Studio is a new creation created by Lya Novrista in 2014. The Pagar Pengantin dance performance took place on the stage at 10:30 a.m. WIB. The Pagar Pengantin dance was performed after the bride and groom, and their families entered the stage. The dance began with four dancers inside the stage, then walked out to meet the bride and groom and their families and guided them to the stage, allowing them to sit in the designated seats. Then the dancers from the outside of the stage enter the stage with right and left crossing footwork to take their places, this dance begins with a respectful cross movement, a movement that means to give honor to the bride and groom, family and invited guests who have attended, followed by the movement of picking up the bride, installing tanggai, respectful cross, amethyst, repel disaster cross, thread stretching, falling wood, scattering flowers, Borobudur, stupa cross, meditation cross, siguntang mahameru cross and flying eagle. Properties are arranged on a tray or gold tray. The number of dancers in the Pagar Pengantin dance must be an even number, namely four female dancers and one main dancer, namely the bride. The Pagar Pengantin dance has a simple "V" floor design with two levels of standing and sitting, followed by a horizontal straight line at the end. The music in the Pagar Pengantin dance uses pre-recorded music (audio recording). The makeup and costumes of the Pagar Pengantin dance use beautiful makeup, the costumes used are baju kurung and wearing a songket skirt. The properties or equipment used are tanggai or gold false nails, candles and a tray or gold tray. This dance is performed as a symbol of the bride's purity and symbolizes the bride's farewell to her former family before starting a new one.